A Comparison of Effectiveness f Betamethasone Gel and Lignocaine Jelly Applied to Tracheal Tube on Postoperative Sore Throat - Hossain, Muhammad Sazzad; Sanjowal, Lipika; Rahman, Md Afzalur; Rashid, Mamunur; Alamgir, Mahiuddin; Waliullah, Md; Babu, Anisur Rahman; Saha, Devashis; Islam, Monirul (Faridpur Medical College Journal, 2019)
Post-operative airway symptoms specially postoperative sore throat (POST) can be troublesome to patients following an uneventful general anesthesia with endotracheal intubation. Ninety ASA I and II informed consenting patients aged 20-50 years were recruited and randomly allocated into three groups of 30 each. The outer surface of the tracheal tubes used in intubating patients were lubricated with 0.05% betamethasone gel for group B, 2% lignocaine jelly for group L from the distal tip of the tube to the 15 cm mark and group C without lubrication. The incidence and severity of sore throat was then assessed at 1 hour, 6 hours and 24 hours during postoperative period. At 24 hours following extubation, there was a statistically significant lower incidence of POST in group B compared to other two groups. (group B= 6.66% vs group L= 33.33% vs group C= 40%, p<0.05). When the groups were compared in pairs, there was a statistically significant difference of POST between groups B and L also groups B and C with lower incidence of POST in group B at 24 hours, p<0.05. Significant difference in incidence of POST was, however, not found when group C was compared with group L separately, at different time of interval, p>0.05. It could be concluded that 0.05% betamethasone gel applied widely over endotracheal tube effectively reduces postoperative sore throat in comparison with 2% lignocaine jelly application. Faridpur Med. Coll. J. Jul 2018;13(2): 58-61